Potret Aktivitas Belajar Mahasiswa Vokasi Kesehatan di Masa Pandemi Covid-19 - Nurbaiti Nurbaiti (SAP (Susunan Artikel Pendidikan), 2022)
The Covid-19 pandemic has accelerated the adaptation of the education sector in utilizing technology and various learning tools in cyberspace. Vocational students at the Department of Radiodiagnostic Engineering and Radiotherapy, Poltekkes Kemenkes Jakarta II, utilize various online learning resources. This research is descriptive qualitative to find out how students learn during the pandemic. The data is collected from questionnaires using WhatsApp in Google-form. From this research, it is discovered that students accessing lectures online are increasing, smartphones are the most frequently used devices for learning. The media used by students are online classes, lecture materials sent online, video tutorials and assignments are given by lecturers and group discussions. Social media is also used as learning media using WhatsApp, Youtube, Instagram and Telegram. Many digital platforms are utilized to access learning materials. Most students are still constrained by unstable internet access in the online-learning. The skills of utilizing digital platforms for learning still need to improve.